The anti-Enlightenment tradition as a common framework of fascism and the contemporary far right - Ziegler, Tamás Dezső (Fascism, 2021)
The relationship between far-right political streams and fascism is a recurring topic in scientific literature. However, we find a low number of academic publications which try to create a framework for their similarities. This article uses Zeev Sternhell’s theory of fascism as a tool to measure different interpretations of fascism and the far right. According to its basic statement, there exists an anti-Enlightenment tradition in the Western world, which could serve as a substratum of these streams. This proves two points. Firstly, that there are several political groups which share a very similar political vision, even if their levels of aggression and radicalism are different. This is the reason why many neo-fascist, post-fascist, ‘populist’ and conservative parties have interchangeable rhetorical clichés and ideological patterns. Second, it shows that Western countries could successfully fight the rise of upcoming anti-democratic forces through strengthening the values of the Enlightenment-tradition.